1, 5, 6, 7-Tetrahydro-4H-indazol-4-ones as human neutrophil elastase (HNE) inhibitors. (15th November 2021) - Cantini, Niccolo; Crocetti, Letizia; Guerrini, Gabriella; Vergelli, Claudia; Schepetkin, Igor A.; Pallecchi, Marco; Bartolucci, Gianluca; Quinn, Mark T.; Teodori, Elisabetta; Giovannoni, Maria Paola
Graphical abstract: Highlights: Human neutrophil elastase (HNE) as diagnostic marker and therapeutic target for some types of cancer. Synthesis of a new series of compounds showing an innovative 1, 5, 6, 7-tetrahydro-4H-indazol-4-one core as HNE inhibitors. Characterization and separation of the pairs of isomers using different techniques. Abstract: Human neutrophil elastase (HNE) is a serine protease that is expressed in polymorphonuclear neutrophils. It has been recognized as an important therapeutic target for treating inflammatory diseases, especially related to the respiratory system, but also for various types of cancer. Thus, compounds able to inhibit HNE are of great interest in medicinal chemistry. In the present paper, we report the synthesis and biological evaluation of a new series of HNE inhibitors with an innovative 1, 5, 6, 7-tetrahydro-4H-indazol-4-one core that was developed as a molecular modification of our previously reported indazole-based HNE inhibitors. Since the 1, 5, 6, 7-tetrahydro-4 H -indazol-4-one scaffold can occur in two possible tautomeric forms, the acylation/alkylation reactions resulted in a mixture of the two isomers, often widely unbalanced in favor of one form. Using analytical techniques and NMR spectroscopy, we characterized and separated the isomer pairs and confirmed the compounds used in biological testing. Analysis of the compounds for HNE inhibitory activity showed that they were potent inhibitors, with Ki values in the low nanomolar range (6–35 nM). They also had reasonable stability in aqueous buffer, with half-lives over 1 h. Overall, our results indicate that the 1, 5, 6, 7-tetrahydro-4H-indazol-4-one core is suitable for the synthesis of potent HNE inhibitors that could be useful in the development of new therapeutics for treating diseases involving excessive HNE activity.